PENGARUH RELAKSASI NAPAS DALAM DENGAN AROMATERAPI LAVENDER TERHADAP TINGKAT NYERI POST APENDIKTOMI DI RUANG JANGER RSD MANGUSADA - Lestari, I Gusti Ayu Dewi Indra; Susila, I Made Dwie Pradnya; Kusuma, A.A. Ngurah Nara (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2021)
Appendectomy is a surgical procedure for appendicitis. This action can cause the perception of pain so that it has an impact on the healing process and triggers further complications if left untreated. Deep breathing relaxation techniques combined with aromatherapy is one of the treatments done to help overcome post appendectomy pain. This study purposed to determine the effect of deep breath relaxation with lavender aromatherapy on the level of post appendectomy pain in the Janger Room RSD Mangusada. This study is a pre-experimental research with one group pretest and posttest design involving 32 samples selected through purposive sampling technique. Collecting data using a research instrument in the form of the Numerical Rating Scale observation sheet. The results showed that there was an effect of deep breath relaxation with lavender aromatherapy on the level of post appendectomy pain in the Janger Room at RSD Mangusada (p-value = 0,000). This research can be applied in the provision of nursing services as one of the nursing interventions to reduce post appendectomy patient pain.